Differential contributions of the gut microbiota and metabolome to pathomechanisms in ulcerative colitis: an in vitro analysis - Poppe, Jonas; Boesmans, Leen; Vieira-Silva, Sara; Deroover, Lise; Tito, Raul; Vandeputte, Doris; Vandermeulen, Greet; De Preter, Vicky; Raes, Jeroen; Vermeire, Severine; Falony, Gwen; Verbeke, Kristin (Gut microbes, 2024)
The gut microbiota has been implicated in onset and progression of ulcerative colitis (UC). Here, we assess potential causal involvement of the microbiota and -associated fecal water (FW) metabolome in altering key functional parameters of the colonic epithelium. Fecal samples were collected from N = 51 healthy controls (HC), N = 36 patients with active UC (UC-A), and N = 41 subjects in remission N = 41 (UC-R). Using in vitro incubation experiments, the FW metabolome's impact on butyrate oxidation rates/gene expression and cell death (cytotoxicity) of HT-29 cells, cytokine production by PBMC, and barrier integrity of Caco2 monolayers was evaluated. The FW metabolome from patients and individuals hosting the Bacteroides 2 (Bact2) enterotype (69% of UC-A, 31% of UC-R, 3% of HC), characterized by lower levels of median- and short-chain fatty acids and furan compounds, left butyrate oxidation rates unaltered but affected associated gene expression profiles. UC patients/Bact2-carriers' FW lowered PBMC IL-8 production and increased IL-1β production. Patients' FW increased cytotoxicity, associated with sulfide compound levels. Bact2 carriers' FW, displaying higher levels of bile acids, lowered barrier function upon incubation of monolayers. The FW metabolome of patients and individuals hosting a dysbiotic microbiota could contribute to the disruption of functional processes of the colonic epithelium as observed in UC. What is already known on this topic. The altered gut microbiota is implicated in the pathology of ulcerative colitis, potentially due to a mediating role of the associated fecal water metabolome. Colonocytes of patients with ulcerative colitis display altered butyrate oxidation rates, gut barrier function, and immune function in vivo. What this study adds. The gut microbiota in ulcerative colitis, characterized by an increased prevalence of the Bacteroides 2 (Bact2) enterotype, is associated with an altered metabolome comprising lower SCFA, MCFA, and furan concentrations and higher levels of bile acids. The UC-associated fecal metabolome alters butyrate oxidation gene expression and cytokine production in colonocytes in vitro. It reduces gut barrier function and results in higher cytotoxicity of fecal water. Changes in butyrate oxidation gene expression and immune function are associated both with disease and Bact2 carrier status. Gut barrier function mainly depends on Bact2 status, while fecal water cytotoxicity reflects disease status. How this study might affect research, practice, or policy. This study demonstrates the impact of the altered fecal water metabolome in ulcerative colitis on functional parameters of the colonic epithelium. By disentangling effects of Bact2 and patient disease status, the study identifies modulation of the gut microbiota away from enterotype-defied dysbiosis as a potential strategy to increase barrier function.